P53 and PIK3CA Mutations in KRAS/HER2 Negative Ovarian Intestinal-Type Mucinous Carcinoma Associated with Mature Teratoma - Sarah Bouri; Philippe Simon; Nicky D’Haene; Xavier Catteau; Jean-Christophe Noël (Case Reports in Obstetrics and Gynecology)
Primary ovarian intestinal-type mucinous carcinomas associated with mature teratoma are rare and represent less than 3% of all primary ovarian neoplasms. The molecular profile of these tumors is still controversial. We report here the first case of mucinous ovarian tumor in which mutation of the PIK3CA and P53 genes could be demonstrated by the next generation sequencing technique without KRAS mutation or HER2 amplification. Our data suggest that these mucinous carcinoma variants probably present an extremely complex molecular biology profile that should be known in the future to stratify therapeutic outcomes and potential targeted therapies, particularly in recurrent disease.